Impact of FDG-PET on the detection of patients with lung cancer at high risk for ILD - Flechsig, Paul; Hural, Olena; Kreuter, Michael; Eichhorn, Martin E.; Heußel, Gudula; Sachpekidis, Christos; Kauczor, Hans-Ulrich; Haberkorn, Uwe; Heußel, Claus Peter; Eichinger, Monika (In vivo, 2018)
BACKGROUND/AIM: Idiopathic pulmonary fibrosis IPF is a type of interstitial lung disease (ILD) with poor prognosis. Lung cancer (LC) is a frequent complication in IPF, where all therapeutic options are potential triggers for acute exacerbation of IPF. - PATIENTS AND METHODS: Patients with 2-deoxy-2-fluoro-D-glucose-positron emission tomography/computer tomography (FDG-PET/CT) results before lobectomy for LC with and without (n=10 each) signs of ILD in initial imaging and after-care CT were retrospectively analyzed. FDG uptake was calculated as the maximum standardized uptake value (SUVmax) in the lung periphery divided by the SUVmax of the mediastinal blood pool (rSUVmax). Regional increase of fibrosis and ground-glass features in lobe-based CT analysis was used as standard reference. - RESULTS: Patients with LC with ILD presented a significantly higher rSUVmax of 0.57 compared to patients without ILD with rSUVmax 0.47 (p<0.001). - CONCLUSION: rSUVmax seems to be a valuable imaging surrogate in predicting patients with LC with increased risk for progressive ILD associated with thoracic surgery.
Gesehen am 24.04.2020